TAFSIR AYAT AL QUR’AN TENTANG QALB (Kajian Tafsir Maudhu’i) - Nurotun Mumtahanah (Akademika, 2019)
The study is about Maudhui's interpretation of the Qur'anic verses relating to the so-called qolb. In various references, qolb means heart and in various languages: heart (English), herz (Germ), Coeur (Franc), Corazon (Spanish), Cuore (Italian), hart (Dutch), serce (Polish) , inima (Rome), dil (Urdu), hreday (Indian), xin (Chinese), maeum (Korean), قَلْبٌ (Arabic). Imam Al-Ghazali believes that the heart is from two aspects, namely the physical and spiritual aspect. The physical heart is the one that is shaped like a banana blossom which is located in the left side of the chest. While the spiritual one is subtle (latif), rabbani, and spiritual that is related to the physical heart. Sufis often call the heart with the following names: (1) baitul-hikmah, which is the heart that wins and produces sincerity; (2) baitul-muqaddas, i.e. outwardly heart that is to do with other people; (3) baitul-muharram, which is a perfect human heart specifically intended to know and love God; (4) baitul-izzah, the heart that arrives at in a mortal condition' (eliminating bad qualities and the effects of cruelty) for solely the sake of Allah; and (5) al-falaq al-mubin, which is the peak level consisting of the human heart. M. Quraish Shihab argues that the heart is part of the nafs, a kind of contact within the nafs, while the nafs itself is the inner side of man. It can also be emphasized that what the scholars agreed is that the heart is not a liver because the organ is known in Arabic with a 'kabid'.